Design of planar mushroom-shaped wideband monopole antenna using Gielis curves - Bhaskar, Vignesh Shanmugam (2021)
This paper presents the design of planar mushroom-shaped wideband monopole antenna using Gielis curves. The Gielis curves are used to design the complex shape profiles of the monopole conveniently. The performance characteristics of the antennasuch as return loss, realized gain and radiation pattern are simulated and the return loss is compared with the measured result. The-10dB impedance bandwidth of the antenna is from 2.5 GHz to 9 GHz and the peak gain is about 3 dB to 4.5 dB.